High fives motivate: the effects of gestural and ambiguous verbal praise on motivation - Morris, Bradley J.; Zentall, Shannon R. (Frontiers in Psychology, 2014)
The type of praise children receive influences whether children choose to persist after failure. One mechanism through which praise affects motivation is through the causal attributions inferred from language. For example, telling a child “You got an A on the test because you’re smart,” provides an explicit link between possessing a trait and an outcome, specifically that intelligence causes success. Nonetheless, most praise given to children is ambiguous, or lacks explicit attributions (e.g., “yea” or a thumbs-up). To investigate the effects of ambiguous praise on motivation, we randomly assigned 95 5-6-year-old children to a praise condition (verbal trait; verbal effort; verbal ambiguous; or gestural) and measured motivation using task persistence, self-evaluations, and eye fixations on errors. Ambiguous praise, similar to verbal effort praise, produced higher persistence and self-evaluations, and fewer fixations on error after failure compared to verbal trait praise. Interestingly, gestures produced the highest self-evaluations. Thus, praise without explicit attributions motivated as well or better than praise explicitly focused on effort.